Further Evaluation of the Scoring, Reliability, and Validity of the Hypertonia Assessment Tool (HAT). (April 2014) - Knights, Shannon; Datoo, Natasha; Kawamura, Anne; Switzer, Lauren; Fehlings, Darcy
We assessed the impact of videotape analysis on scoring of the Hypertonia Assessment Tool (HAT) that discriminates between hypertonia subtypes. The HAT was administered to 28 children with cerebral palsy (mean age 9 years, range 4-17 years, 61% male). HAT examinations were videotaped; scores were assigned before and after videotape review. Neurological examination provided the gold standard diagnosis. Interrater reliability, criterion validity and individual item validation were assessed using prevalence and bias-adjusted kappa (PABAK). Videotape review did not significantly change the HAT item scores or diagnoses. Item validation eliminated 1 dystonia item. Interrater reliability was moderate for dystonia (PABAK = 0.43) and excellent for spasticity and rigidity (PABAK = 0.86-1.0). Criterion validity was substantial for spasticity (PABAK = 0.71), moderate for dystonia (PABAK = 0.43-0.57) and excellent for the absence of rigidity (PABAK = 1.0). The HAT can be administered without videotape review. Dystonia item 1 did not change the HAT hypertonia diagnosis and will be removed from the HAT.